PENGARUH KOMBINASI PUPUK HIJAU Azolla pinnata R.BR. DENGAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa L.) - Muhammad Mahrupi; Armaini '; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
A research has done on the effect of the combination green manure Azolla pinnata R.Br. with chicken manure toward the growth and production of lettuce (Lactuca sativa L.) in the experiment garden of Agriculture Faculty in University of Riau. The aim of this research is to determine or to know the best combination of Azolla pinnata provision of green manure with chicken manure on the growth and production of lettuce in two planting periods. The research was conducted with two planting periods and experimentally by using completely randomized design with seven treatments that consists of : P0 = no treatment, P1 = 5 tons of Azolla + 10 tons of chicken manure, P2 = 5 tons of Azolla + 15 ton of chicken manure, P3 = 10 tons of Azolla + 10 tons of chicken manure, P4 = 10 tons of Azolla + 15 tons of chicken manure, P5 = 15 tons of Azolla + 10 tons of chicken manure, P6 = 15 tons of Azolla + 15 tons of chicken manure. The result of the research showed combination treatment influential significantly affected all parameters and treatment 15 tons/ha of Azolla with 10 tons/ha of chicken manure give a the best result on the all planting. The result of the research showed a decrease in each parameters on the second planting. Key words : Azolla, chicken manure, lettuce